A study of the teething problem of procuring entity on electronic government procurement (e-GP) operation system - Ahsan, Md. Ashiful (BRAC Univeristy, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.